HERMENEUTIKA AL-QUR’AN DR. ALI ABDUL HALIM MAHMUD (W. 2014) DALAM MENGEMBANGKAN TAFSIR PENDIDIKAN ISLAM - Mahmud Arif (Jurnal Pendidikan Agama Islam, 2016)
The future of Moslems are stimulated by the Qur’anic interpretation that is always renewed, so allendeavors to comprehend the Holy Qu’ran are important and crucial duty. According to those, AliAbdul Halim Mahmud (AAHM) has built seriousely a firm conviction on the perfection of the Qur’anand the necessity for Moslems in obeying to it. The only way to solve any problem caused them goingastray in this life is return to guidance of the Qur’an and the Prophet tradition.AAHM has utilizedtwo models in elaborating the Qur’anic tenets, i.e. : (1) selecting a certain surah to be interpreted,and (2) appointing a certain educational topic and explaining the relevant content of Qur’anic verses.Those models stand on assumption that as a guidance book, there is no matter in life that’s neglectedin the Qur’an. His belief in an existence of the perfect Qur’anic educational system has promptedhim to endeavour in describing prescriptions of the Qur’anicverses so those became as educationalperspectives or viewpoints, either with nuance of clarifying, comparing or perfecting, that contain fullymessages of moral, religious preaching, and movement in order to revive the glory of Islam.Keywords: Islam as a complete system, special characteristics of the Qur’an, Qur’anic educationalsystem, model of Qur’anic interpretation.